Kemenangan Royal Simanjuntak dari Partai Kebangkitan Bangsa menjadi Anggota DPRD Kabupaten Tapanuli Utara - Terri Genta Sansui Siregar; Subillhar Subillhar; Heri Kusmanto (Universitas Medan Area, 2022)
The purposes of this study are: To find out the victory and electability factor of Royal Simanjuntak from PKB to become a Member of the DPRD of North Tapanuli Regency in the 2019 Election To understand the electability factor of Royal Simanjuntak in the 2019 Election. The type of this research is qualitative research. The strategy carried out by Royal Simanjuntak in his victory in the 2019 Legislative Election is by maximizing 9 elements of political marketing, the 9 elements are segmentation, positioning, policy, person, party, presentation, pull marketing, pass marketing and push marketing. Using political marketing strategies through political communication channels, namely, face-to-face and door-to-door activities. This door to door strategy is very effective and helps the process of attracting prospective voters because apart from being known to prospective voters, Royal can directly discuss and witness the situation of the community more closely. Royal Simanjuntak!'s victory in the 2019 election, apart from a good political marketing strategy, was also influenced by Royal's socio-political modalities. Socio-political modalities in the form of political capital, social capital and economic capital are very effective in winning political contestations. conceptually it is said that the synergy of these three socio-political modalities is very significant in influencing the victory of a candidate. The modalities that were managed and organized effectively by Royal simanjuntak had a significant influence on its victory in the 2019 elections.